In vivo Mechanical Characterization of Ascending Aortas from Magnetic Resonance Imaging. - Latorre Molins, Álvaro Tomás; Guala, Andrea; Dux-Santoy Hurtado, Lydia; Teixidó Turà , Gisela; Rodríguez Palomares, José Fernando; Martinez Barca, Miguel Ángel; Peña Baquedano, Estefanía (Jornada de Jóvenes Investigadores del I3A, 2024)
Ascending aortic aneurysm is a normally asymptomatic but fatal pathology that requires early follow-up to avoid major complications. In this work, we present a methodology to obtain unpressurized ascending aortic geometry and its nonlinear anisotropic properties from medical imaging.